2007
DOI: 10.1242/dev.000885
|View full text |Cite
|
Sign up to set email alerts
|

The FERM protein Epb4.1l5 is required for organization of the neural plate and for the epithelial-mesenchymal transition at the primitive streak of the mouse embryo

Abstract: During early mouse development, a single-layered epithelium is transformed into the three germ layers that are the basis of the embryonic body plan. Here we describe an ENU-induced mutation, limulus (lulu), which disrupts gastrulation and the organization of all three embryonic germ layers. Positional cloning and analysis of additional alleles show that lulu is a null allele of the FERMdomain gene erythrocyte protein band 4.1-like 5 (Epb4.1l5). During gastrulation, some cells in lulu mutants are trapped in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 41 publications
8
91
0
Order By: Relevance
“…First, we examined the nuclear morphology as an indicator of cell shape, using TOTO-3 staining ( Fig. 2 E and FЈ), because the dense cell packing within the epiblast hampers the direct examination of cell shape using cytoskeletal labeling, but nuclear shape varies with cell shape as a function of the cytoskeleton (22). We found that the control nuclei were ellipsoid and elongated along the AB axis, with an average length-to-width ratio of 2.49 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, we examined the nuclear morphology as an indicator of cell shape, using TOTO-3 staining ( Fig. 2 E and FЈ), because the dense cell packing within the epiblast hampers the direct examination of cell shape using cytoskeletal labeling, but nuclear shape varies with cell shape as a function of the cytoskeleton (22). We found that the control nuclei were ellipsoid and elongated along the AB axis, with an average length-to-width ratio of 2.49 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A) (Baines, 2006;Lee, J. D. et al, 2007;Shimizu et al, 2000). The C-terminal portions of the isoforms do not have obvious homology among them.…”
Section: Resultsmentioning
confidence: 99%
“…Lulu1 mutant mice were reported to exhibit defects in shaping ingressing cells during gastrulation: Although ingressing cells normally exhibited a bottle-shaped morphology, the cells in mutant mice displayed a rounded morphology (Lee, J. D. et al, 2007). In another previous report, it was proposed that Lulu1 regulates the state of classic cadherins and integrins, and that their misregulation might be responsible for defects in gastrulation in mutants (Hirano et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of Sox2, a marker of neuroepithelia (Collignon et al, 1996) (George et al, 1993;Yang et al, 1993;Lee et al, 2007). Therefore, some of the neuroepithelial defects of Ddx11 cetus mutants might originate from the lack of somitic mesoderm.…”
Section: Loss Of Ddx11 Function Causes Depletion Of Somitic Mesodermmentioning
confidence: 99%